Water Quality and Plankton Assemblages in Eniong Creek: Implications for Biodiversity and Anthropogenic Influence - Imaobong E. Ekpo,; Udeme E. Jonah,; Emeka D. Anyanwu, (Journal of Science and Technology, 2025)
The water quality and plankton assemblages of Eniong Creek were studied between August 2022 and January 2023 in three sampling points. Plankton and water samples were collected monthly using plankton net and water sampler. The water and plankton samples were analyzed using standard laboratory techniques. The results showed that some values of pH, PO-4, BOD5 and all TSS, and DO did not conform to the acceptable limits. A total of 33 species of phytoplankton from three taxonomic classes were recorded: dominated by Baccillariophyceae with 17 species and 401 individuals (59.8%). A total of 26 zooplankton species from four taxonomic classes were recorded. Monogononta (Rotifar) was the most dominant and abundant class with 12 species and 357 individuals (47.1%). Melosira granulata was the most abundant phytoplankton species (36, 5.4%), while Lecane bulla was the most abundant zooplankton species (62, 8.2%). The biodiversity- Margalef’s index: 4.769-4.963 (Phytoplankton) and 3.711- 4.109 (Zooplankton), Shannon-Weiner index: 3.075 (Phytoplankton) and 2.85-2.99 (Zooplankton), and Pielou Evenness index: 0.802-0.874 (phytoplankton) and 0.799-0.842 (Zooplankton) suggest moderate. It can be concluded that the composition, abundance and distribution of plankton in was influenced by the physicochemical conditions of the Creek, which in turn was influenced by human activities.